The cloud : understanding the security, privacy and trust challenges - Robinson, Neil, 1964- (Technical report (Rand Corporation) ;, 2011)
This report discusses how policy-makers might address the challenges and risks in respect of the security, privacy and trust aspects of cloud computing that could undermine the attainment of broader economic and societal objectives across Europe.